Epidermal autophagy and beclin 1 regulator 1 and loricrin: a paradigm shift in the prognostication and stratification of the American Joint Committee on Cancer stage I melanomas. (19th June 2019) - Ellis, R.; Tang, D.; Nasr, B.; Greenwood, A.; McConnell, A.; Anagnostou, M.E.; Elias, M.; Verykiou, S.; Bajwa, D.; Ewen, T.; Reynolds, N.J.; Barrett, P.; et al.
Summary: Background: The updated American Joint Committee on Cancer (AJCC) staging criteria for melanoma remain unable to identify high‐risk stage I tumour subsets. Objectives: To determine the utility of epidermal autophagy and beclin 1 regulator 1 (AMBRA1)/loricrin (AMLo) expression as a prognostic biomarker for AJCC stage I cutaneous melanoma. Methods: Peritumoral AMBRA1 expression was evaluated in a retrospective discovery cohort of 76 AJCC stage I melanomas. AMLo expression was correlated with clinical outcomes up to 12 years in two independent powered, retrospective validation and qualification cohorts comprising 379 AJCC stage I melanomas. Results: Decreased AMBRA1 expression in the epidermis overlying primary melanomas in a discovery cohort of 76 AJCC stage I tumours was associated with a 7‐year disease‐free survival (DFS) rate of 81·5% vs. 100% survival with maintained AMBRA1 ( P < 0·081). Following an immunohistochemistry protocol for semi‐quantitative analysis of AMLo, analysis was undertaken in validation ( n = 218) and qualification cohorts ( n = 161) of AJCC stage I melanomas. Combined cohort analysis revealed a DFS rate of 98·3% in the AMLo low‐risk group ( n = 239) vs. 85·4% in the AMLo high‐risk cohort ( n = 140; P < 0·001). Subcohort multivariate analysis revealed that an AMLo hazard ratio (HR) of 4·04 [95% confidence interval (CI) 1·69–9·66; P = 0·002] is a stronger predictor of DFS than Breslow depth (HR 2·97, 95% CI 0·93–9·56; P = 0·068) in stage IB patients. Conclusions: Loss of AMLo expression in the epidermis overlying primary AJCC stage I melanomas identifies high‐risk tumour subsets independently of Breslow depth. What's already known about this topic? There is an unmet clinical need for biomarkers of early‐stage melanoma. Autophagy and beclin 1 regulator 1 (AMBRA1) is a proautophagy regulatory protein with known roles in cell proliferation and differentiation, and is a known tumour suppressor. Loricrin is a marker of epidermal terminal differentiation. What does this study add? AMBRA1 has a functional role in keratinocyte/epidermal proliferation and differentiation. The combined decrease/loss of peritumoral AMBRA1 and loricrin is associated with a significantly increased risk of metastatic spread in American Joint Committee on Cancer (AJCC) stage I tumours vs. melanomas, in which peritumoral AMBRA1 and loricrin are maintained, independently of Breslow depth. What is the translational message? The integration of peritumoral epidermal AMBRA1/loricrin biomarker expression into melanoma care guidelines will facilitate more accurate, personalized risk stratification for patients with AJCC stage I melanomas, thereby facilitating stratification for appropriate follow‐up and informing postdiagnostic investigations, including sentinel lymph node biopsy, ultimately resulting in improved disease outcomes and rationalization of healthcare costs. Abstract : Plain language summary available online Linked Editorial: Craig and Virós. Br J Dermatol 2020; 182 :5–6.